APPLICATION OF LEARNING TO STUDENTS USING THE PQ (QUIZ GAME) METHOD - Mawar Maharani; Sulastriana J.Sapondan; Shafira Khairunissa Podungge; Dwi Erninda Puspita; Abdul Rahmat (Scholar Express Journal, 2022)
Selection of learning methods in a learning process can affect student learning outcomes and the atmosphere in the teaching and learning process. Through a game, students can experience teaching and learning activities in a relaxed and fun way. In addition, games can also assist in developing students' skills through the playing process, such as game sequences, verbal, visual, kinetic skills, and other game-based activities. We carried out the quiz game method at SD 2 in West City to find out the use of quiz games and improve students' ability to count as well as increase students' enthusiasm for learning and develop basic knowledge of mathematics, so that children are mentally ready to take part in further mathematics learning. We did this project at SD 2, West City, using a qualitative research method with a descriptive design. Conclusion: there are some students who are not fluent in calculations and subtraction. Perhaps this is due to the lack of students' understanding of the concept of learning. Suggestion: teachers can use easy and fun learning methods or interesting learning media so that they can foster interest in students to be even more enthusiastic about learning.
Keywords: Learning; g, interest and creativity in PQ; Quiz Game